(untitled) (jornal of the libyan geographical society, 2016)
Agriculture is an important economic and political occupation for human life, because it is the primary occupation for many of the world’s inhabitants, and because it provides food for humans. The word farm has come to mean crop cultivation, dairy and meat production farms, poultry farms, and even fishing. Agriculture is also an economic activity because it produces raw materials for industry, such as cotton, sugarcane, beets, and other crops that are used directly or indirectly in industry. Even its byproducts can be an economic driver, such as using sugarcane residue as energy for the same industry and for electricity production. There is also the plant *Rapeseed*, from which biogas oil is extracted. To manage some engines. The Kufra production project is one of the leading projects in Libya, as it enjoys great environmental potential, represented by the fertile and bountiful land, and the abundant groundwater which, if exploited in a balanced way without excessive use, can irrigate thousands of hectares over hundreds of years, which promises a good future if the difficulties facing the project are overcome.